Perceptions of Traffic Congestion among Two-Wheeler Users in Kathmandu Valley (The Harvest, 2026)
In the Kathmandu Valley, traffic congestion is common problem to the travelers. Rapid urbanization, rising ownership of private vehicles, and insufficient road infrastructure, the road users are facing highly congested traffic, with frequent delays, wastage of fuel, and stress due to prolonged jams. The major objectives of the study included analyzing the time lost by two-wheeler riders due to traffic congestion and estimating the extra cost of fuel due to such delays. This study was a quantitative study that utilized descriptive and inferential designs. Primary data were gathered from 534 users of two-wheelers. Descriptive statistics, correlation, and multiple regression analyses were applied in testing the association between the dependent variables (time loss and fuel cost) and independent variables including the density of the traffic flow, narrow road, weather, driver attitudes, and efficiency in the traffic signal. On average, it is estimated that two-wheeler users lose about 11,730.25 minutes in a year due to congestion; this time is valued at approximately NRS 13,601.75 annually. Similarly, it has additional cost of NRS16501.25 per year as additional fuel cost. Almost 30,000 NRS is loosed by a single two-wheeler in this research paper.